Theoretical Basis for Primary School Education in the Process of Forming Schools (Journal of Pedagogical Inventions and Practices, 2022)
During the colonial era , the courage shown by the pilgrims in the formation of new schools, the textbooks they developed, publications, and articles were compiled regulations, their activities in fundamental reform of education